Management of Spreading Pricklypear (Opuntia humifusa) with Fluroxypyr and Aminopyralid. (December 2014) - Ferrell, Jason; Sellers, Brent; Leon, Ramon
Abstract : Experiments were conducted throughout central Florida from 2010 to 2014 to determine the effectiveness of fluroxypyr or aminopyralid for control of spreading pricklypear. Aminopyralid + 2, 4-D (0.09 + 0.75 kg ae ha −1 ) was not effective and provided only 15% control by 18 mo after application (MAT). However, fluroxypyr at 0.55 kg ae ha −1 or sequential applications of 0.27 kg ha −1 provided greater than 82% control at 18 MAT. Reducing fluroxypyr rates to 0.32 kg ha −1 reduced control to 40 and 71% for spring versus fall applications, respectively. However, the addition of aminopyralid + 2, 4-D to fluroxypyr at 0.32 kg ha −1 improved pricklypear control to 92%, regardless of application timing.